Epidemiology and implications of concurrent diagnosis of eosinophilic oesophagitis and IBD based on a prospective population-based analysis. Issue 12 (28th March 2019) - Limketkai, Berkeley N; Shah, Shailja C; Hirano, Ikuo; Bellaguarda, Emanuelle; Colombel, Jean-Frederic
Abstract : Objective: Eosinophilic oesophagitis (EoO) and IBD are immune-mediated diseases of the gastrointestinal tract with possible overlapping pathogenic mechanisms. Our aim was to define the epidemiology and clinical implications of concurrent EoO and IBD diagnoses. Design: We conducted a prospective cohort analysis using the Truven MarketScan database (2009–2016) to estimate the incidence and prevalence of EoO in patients with Crohn's disease (CD) or UC and vice versa. Cox proportional hazards and Kaplan-Meier methods were used to estimate the risk of EoO-related or IBD-related complications among patients with concurrent diagnoses. Results: Among 134 013 536 individuals, the incidence of EoO, CD and UC were 23.1, 51.2 and 55.2 per 100 000 person-years, respectively. The risk of EoO was higher among patients with CD (incidence rate ratio [IRR] 5.4, p<0.01; prevalence ratio (PR) 7.8, p<0.01) or UC (IRR 3.5, p<0.01; PR 5.0, p<0.01), while the risk of IBD was higher among patients with EoO (CD: IRR 5.7, p<0.01; PR 7.6, p<0.01; UC: IRR 3.4, p<0.01; PR 4.9, p<0.01) versus individuals without either diagnosis. Concurrent diagnosis of EoO and IBD was associated with greater composite risk of IBD-related complications (CD: adjusted HR (aHR) 1.09, p=0.01; UC: aHR 1.10, p=0.04) but lower composite risk of EoO-related complications (aHR 0.59; p<0.01). Conclusion: Based on a population-based prospective cohort analysis, the risk of EoO is significantly higher among patients with IBD and vice versa. Concurrent diagnoses might modify the risk of IBD-related and EoO-related complications. Studies defining the mechanisms underlying these observations are needed.